Water Table Drawdown Alters Soil and Microbial Carbon Pool Size and Isotope Composition in Coastal Freshwater Forested Wetlands - Minick, Kevan J.; Mitra, Bhaskar; Li, Xuefeng; Noormets, Asko; King, John S. (Frontiers in Forests and Global Change, 2019)
Loss of coastal wetlands is occurring at an increasingly rapid rate due to drainage of these wetlands for alternative land-uses, which also threatens carbon (C) storage in these C-rich ecosystems. Wetland drainage results in water table drawdown and increased peat aeration, which enhances decomposition of previously stabilized peat and changes stable C isotope profiles with soil depth. The effect of water table drawdown on the pool size and δ13C signature of plant C, soil organic C (SOC) and microbial biomass C (MBC) across a range of organic and mineral soils has not previously been reported in coastal freshwater forested wetlands. To this end, litter, roots, and soils were collected from organic and mineral soil horizons in two coastal freshwater forested wetlands in North Carolina with different hydrological regimes: 1) a natural bottomland hardwood forest (natural); and 2) a ditched and drained, intensively-managed wetland for loblolly pine silviculture (managed). We found that hydrology and soil horizon, and to a lesser degree micro-topography, was important in shaping observed differences in size and 13C signature of soil and microbial pools between the natural and managed wetland. The natural wetland had higher SOC and MBC concentrations in the litter, surface organic, and mineral horizons compared to the managed wetland. In the managed wetland, 13C of SOC was enriched across most of the soil profile (Oa and mineral soil horizons) compared to the natural wetland, suggesting enhanced decomposition and incorporation of microbially-derived inputs to soils. Root C concentration decreased with soil depth, while root 13C signature became enriched with soil depth. In the litter and Oe horizon of the natural wetland, MBC was higher and 13C of MBC and SOC was enriched in hummocks compared to hollows. The 13C of MBC and SOC tended to be enriched in upper soil horizons and depleted in lower soil horizons, particularly in the managed wetland. We conclude that drainage of these coastal wetlands has enhanced the breakdown of previously stabilized C and has the potential to alter regional C storage, feedbacks to climate warming, and ecosystem responses to changing environmental conditions.